Is there a link between motor vehicle collisions and being a cigarette smoker in Canada? Analysis of survey data from Ontario from 2002 to 2014. (19th May 2018) - Vingilis, Evelyn; Pederson, Linda L.; Seeley, Jane; Ialomiteanu, Anca R.; Wickens, Christine M.; Ferrence, Roberta; Mann, Robert E.
ABSTRACT: Objective : Although most research on drugs and driving has focused on the use of alcohol and cannabis, research that has been conducted on cigarette smoking and collisions has found that smokers have an increased collision involvement. Studies dating from 1967 through 2013 have shown a crude relative risk of about 1.5 among smokers compared to nonsmokers. In Canada, the association between smoking and collisions has not been recently investigated. Studies that have examined the association between smoking and collisions often did not control for all confounding factors, such as alcohol use and driving exposure, which have been associated with increased collision rates. Additionally, a number of these studies were examined in countries and at times when prevalence of smoking was much higher than is currently the case in Canada. The purpose of this research is to examine the association between self-reported current smoking and past-year collision involvement, controlling for confounding factors, in a large representative sample of adult drivers in Ontario, Canada, from 2002 and 2014. Method : Data are based on the Centre for Addiction and Mental Health (CAMH) Monitor, an ongoing, rolling telephone survey of Ontario adults that provides epidemiological surveillance of indicators related to alcohol, tobacco, and other drug use, as well as physical and mental health. The survey uses random-digit-dialing methods via Computer-Assisted Telephone Interview, with response rates over 50%. Results : Prevalence of self-reported collision involvement within the past year for 2002–2014 was 8.6% among those who currently smoke compared to 6.5% of nonsmokers. Logistic regression analysis, controlling for the potential confounding effects of sociodemographics, driving exposure measures, drinking frequency, and hazardous alcohol use, found that the overall odds for collision involvement in the preceding year among current smokers for 2002–2014 was 1.27 (95% confidence interval [CI], 1.06–1.53) times that of nonsmokers. Conclusions : These findings indicate that despite a substantial reduction in overall prevalence of smoking in Canada, smokers still have a significantly increased odds of collision involvement, even when controlling for alcohol and exposure. Additionally, the results are consistent with the increased odds/risks of motor vehicle collisions found in other countries.